Human Rights Approach to First Call for Children: Mapping the Perils and Promises in South Asia - Sangroula, Geeta Pathak (Kathmandu School of Law Review, 2022)
The Convention on the Rights of the Child (CRC) is regarded as one of the most successful human rights treaties for its substance and global acceptance. Being in a row among the highest number of State parties, all South Asian countries promised to respect, protect, and fulfill children's rights. However, the socio-legal constraints and deficits in practical implementation measures have caused setbacks in protecting child rights. This paper aims to explore the historical antecedents of international human rights standards developed step-by-step that contributed to adopting the Convention on the Rights of the Child (CRC). This article navigates the implementation of the provisions enshrined in the CRC, following the essence of the ‘first call for children’ as echoed by the Vienna Declaration and Programme of Action in 1993. The paper aims to reflect the international and regional legal standards incorporated in the domestic laws of South Asian countries. It further intends to focus on a comparative analysis of the legal mechanisms, socio-economic, and political situation regarding child rights with particular reference to the situation and condition of child rights in the South Asian region.